2004
DOI: 10.1074/jbc.m401716200
|View full text |Cite
|
Sign up to set email alerts
|

Flavocytochrome P450 BM3 Mutant A264E Undergoes Substrate-dependent Formation of a Novel Heme Iron Ligand Set

Abstract: A conserved glutamate covalently attaches the heme to the protein backbone of eukaryotic CYP4 P450 enzymes. In the related Bacillus megaterium P450 BM3, the corresponding residue is Ala 264 . The A264E mutant was generated and characterized by kinetic and spectroscopic methods. A264E has an altered absorption spectrum compared with the wild-type enzyme (Soret maximum at ϳ420.5 nm). Fatty acid substrates produced an inhibitor-like spectral change, with the Soret band shifting to 426 nm. Optical titrations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
101
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(118 citation statements)
references
References 70 publications
16
101
1
Order By: Relevance
“…S9), a slightly longer wavelength than has been observed for other P450s analyzed to date (e.g. ϳ1080 nm for P450 BM3) (32). This suggests that the t 2 g heme iron D-orbitals are closer in energy to the porphyrin orbitals in XplA than is typical in the Cys thiolate-coordinated P450s, possibly due to the electrostatic environment of the thiolate ligand.…”
Section: Interactions Of Xpla With Trinitrobenzene and Other Ligands-mentioning
confidence: 53%
See 1 more Smart Citation
“…S9), a slightly longer wavelength than has been observed for other P450s analyzed to date (e.g. ϳ1080 nm for P450 BM3) (32). This suggests that the t 2 g heme iron D-orbitals are closer in energy to the porphyrin orbitals in XplA than is typical in the Cys thiolate-coordinated P450s, possibly due to the electrostatic environment of the thiolate ligand.…”
Section: Interactions Of Xpla With Trinitrobenzene and Other Ligands-mentioning
confidence: 53%
“…The polar imidazole is usually a weak inhibitory ligand for P450s, although substituted imidazoles can be much tighter binding as a consequence of their more apolar nature and favorable interactions of their substituent groups with active site amino acid side chains. For instance, the P450 BM3 K d for imidazole is several mM, whereas the K d values for 4-phenylimidazole and the fatty acid derivative 12-(imidazolyl)dodecanoic acid are 0.85 and 8 M, respectively (32,43). In order to explore further whether imidazole might be retained by XplA upon protein purification, we performed more extensive dialysis with several buffer changes following the Ni-NTA chromatography step.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is significant that the conserved Glu residue responsible for covalent attachment of the heme to the protein in the P450 4A family is not found in CYP52A21 (Fig. 1) [27]. Indeed, heme staining by adding 3,3',5,5'-tetramethylbenzidine and H 2 O 2 to an SDS-Page gel showed that CYP52A21 does not have a covalently bound heme, in contrast to CYP4A1 which, as expected, does contain the proteinbound heme (supplementary Fig.…”
Section: Sequence Alignment With Other P450smentioning
confidence: 99%
“…A final purification step by fast protein liquid chromatography using Q-Sepharose resin (under the same conditions as used for the lowpressure chromatographic purification described in the accompanying article (17)) was used to produce homogeneous enzyme for crystallographic studies.…”
Section: Mutagenesis Expression and Purification Of Mutant P450 Bm3-mentioning
confidence: 99%
“…To investigate the possibility of creating a similar protein-heme link in the related P450 BM3 heme domain, the A264E mutant was created. Although no covalent modification of the heme was observed, this mutant has several unique features (see accompanying article (17)). In the fatty acid-free form, Glu 264 ligates the heme iron in a proportion of the molecules, creating a novel thiolate-carboxylate ligation that is pushed toward full ligation by binding of the substrate.…”
mentioning
confidence: 99%